2014
DOI: 10.1021/jp507783d
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Glycosylase and β-Lyase Activity Facilitated by Proline: Applications to FPG and Comparisons to hOgg1

Abstract: Quantum mechanical methods are used to investigate the chemical steps during the bifunctional (glycosylase and β-lyase) activity of bacterial FPG DNA glycosylase, which removes the major oxidation product (8-oxoguanine) from DNA as part of the base excision repair process. To facilitate investigation of all potential pathways, the smallest chemically relevant model is implemented, namely a modified OG nucleoside-3'-monophosphate and a truncated proline nucleophile. Potential energy surfaces are characterized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 79 publications
6
37
1
1
Order By: Relevance
“…1b); quantum mechanics/molecular mechanics (QM/MM) simulations show that O4′ protonation provides a low-barrier path to glycosidic bond cleavage by Fpg and its eukaryotic functional analog, OGG1 [33, 36, 68]. From several structures Fpg–DNA complexes, it has been suggested that the proton is shuttled from N[Pro1] to Oε2[Glu2], perhaps through a network of crystallographic water molecules present in the active site [19, 26]; this possibility was also favored by QM/MM analysis [69]. However, no attempt to estimate p K a of Pro1 and Glu2 has been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…1b); quantum mechanics/molecular mechanics (QM/MM) simulations show that O4′ protonation provides a low-barrier path to glycosidic bond cleavage by Fpg and its eukaryotic functional analog, OGG1 [33, 36, 68]. From several structures Fpg–DNA complexes, it has been suggested that the proton is shuttled from N[Pro1] to Oε2[Glu2], perhaps through a network of crystallographic water molecules present in the active site [19, 26]; this possibility was also favored by QM/MM analysis [69]. However, no attempt to estimate p K a of Pro1 and Glu2 has been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…This component was built from the ring-opened deoxyribose intermediate optimized in our previous study 28 by replacing the 5 0 -methoxy group with a 5 0 -phosphate group. This component was built from the ring-opened deoxyribose intermediate optimized in our previous study 28 by replacing the 5 0 -methoxy group with a 5 0 -phosphate group.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] Previous computational work includes molecular dynamics simulations of the anti (w defined as +(O4 0 -C1 0 -N9-C4) equals 180 AE 901) and syn (w = 0 AE 901) conformers of OG, (unmodified) G and several other lesions (such as FapyG, 4,6-diamino-5-formamidopyrimidine (FapyA), and 7,8-dihydro-8-oxoadenine (8-oxoA)) bound in the FPG active site, which shed light on the lesion binding modes and substrate interactions in the recognition pocket. [28][29][30][31][32][33][34][35] Previous computational work includes molecular dynamics simulations of the anti (w defined as +(O4 0 -C1 0 -N9-C4) equals 180 AE 901) and syn (w = 0 AE 901) conformers of OG, (unmodified) G and several other lesions (such as FapyG, 4,6-diamino-5-formamidopyrimidine (FapyA), and 7,8-dihydro-8-oxoadenine (8-oxoA)) bound in the FPG active site, which shed light on the lesion binding modes and substrate interactions in the recognition pocket.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations